Pengaruh Strategi Penetapan Harga Terhadap Minat Beli Konsumen: Studi Kasus Produk Mie Sedaap Goreng di Toko Anita - Andi Bau Salman; Aliana; Fuji Pratiwi (Precise Journal of Economic, 2025)
Pricing is the process of determining the selling price of a product or service offered by a company to consumers. This study aims to determine whether the pricing strategy has a partial effect on consumer purchasing interest at Anita's store. The population in this study were consumers at Anita's Store. And the sample in this study amounted to 100 respondents. This study is a study that uses a quantitative approach and in collecting data used a questionnaire method. Data analysis techniques use quantitative descriptive analysis, validity test, reliability test, t-test, F-test, R-Square test and simple linear regression analysis. The results of the study obtained a t-count value = 13.107 which means the t-count value (13.107)> t-table (1.660) with a significance value of 0.000 <0.05. Thus H0 is rejected and H1 is accepted. This means that there is a significant influence between the pricing strategy variable on consumer purchasing interest at Anita's Store. In addition, from the results of the F test, the F-count value = 171.792 was obtained with a significance value of 0.000 < 0.05, greater than the F-table = 3.94, so it was concluded that H0 was rejected and H1 was accepted. Based on the results of the determination test, the R Square was obtained at 0.637. This value indicates that 63.7% of the factors that influence consumer purchasing interest are pricing, while the rest (36.3%) are influenced by other factors